Effects of four potent entomopathogenic fungal isolates on the survival and performance of Telenomus remus, an egg parasitoid of fall armyworm - Chepkemoi, Junitor; Fening, Ken Okwae; Ambele, Felicitas Chaba; Munywoki, Joseph; Akutse, Komivi Senyo (Frontiers in Cellular and Infection Microbiology, 2024)
Fall armyworm (FAW), Spodoptera frugiperda is a generalist pest known to feed on more than 300 plant species, including major staple crops such as rice, maize and sorghum. Biological control of FAW using a combination of a major indigenous egg parasitoid Telenomus remus and entomopathogenic fungi was explored in this study. Metarhizium anisopliae strains (ICIPE 7, ICIPE 41, and ICIPE 78) and Beauveria bassiana ICIPE 621 which demonstrated effectiveness to combat the pest, were evaluated through direct and indirect fungal infection to assess their pathogenicity and virulence against T. remus adults, S. frugiperda eggs and their effects on T. remus parasitism rates. Metarhizium anisopliae ICIPE 7 and ICIPE 78 exhibited the highest virulence against T. remus adults with LT50 values >2 days. ICIPE 7 induced the highest T. remus mortality rate (81.40 ± 4.17%) following direct infection with dry conidia. Direct fungal infection also had a significant impact on parasitoid emergence, with the highest emergence rate recorded in the M. anisopliae ICIPE 7 treatment (42.50 ± 5.55%), compared to the control ± (83.25 ± 5.94%). In the indirect infection, the highest concentration of 1 x 109 conidia ml-1 of ICIPE 78 induced the highest mortality (100 ± 0.00%) of T. remus adults, and the highest mortality (51.25%) of FAW eggs, whereas the least FAW egg mortality (15.25%) was recorded in the lowest concentration 1 x 105 conidia ml-1 of ICIPE 41. The number of parasitoids that emerged and their sex ratios were not affected by the different fungal strain concentrations except in ICIPE 7 at high dose. This study showed that potential combination of both M. anisopliae and B. bassiana with T. remus parasitoid can effectively suppress FAW populations.